2016
DOI: 10.1136/archdischild-2015-310228
|View full text |Cite
|
Sign up to set email alerts
|

Treatment options for apnoea of prematurity

Abstract: Apnoea of prematurity (AOP) affects almost all infants born at <28 weeks gestation or with birth weight <1000 g. When untreated, AOP may be associated with negative outcomes. Because of these negative outcomes, effective treatment for AOP is an important part of optimising care of preterm infants. Standard treatment usually involves xanthine therapy and respiratory support. Cutting-edge work with stochastic vibrotactile stimulation and new pharmaceutical agents continues to expand therapeutic options. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 41 publications
0
28
1
3
Order By: Relevance
“…The first choice pharmacological agents for the treatment of AOP are methylxanthines: caffeine, theophylline or aminophylline . Methylxanthines stimulate the respiratory system, thereby reducing apnoea.…”
Section: Introductionmentioning
confidence: 99%
“…The first choice pharmacological agents for the treatment of AOP are methylxanthines: caffeine, theophylline or aminophylline . Methylxanthines stimulate the respiratory system, thereby reducing apnoea.…”
Section: Introductionmentioning
confidence: 99%
“…AOP is a common and troublesome disorder which requires intervention to avoid potential morbidity in premature infants who need neonatal intensive care (15). The pathogenesis of apnea is due to immaturity of the respiratory control systems characterized by an abnormal ventilatory response to carbon dioxide and hypoxia combined with immature reflex responses (16).…”
Section: Discussionmentioning
confidence: 99%
“…These issues can be overcome when the tactile stimulation (and/or increasing the oxygen) is applied automatically. Studies have demonstrated that automatic vibrotactile stimulation decreased the occurrence and duration of apneas in preterm infants (15). However, further research is still needed and devices for automatic stimulation are not yet available for clinical use.…”
Section: Apnea Of Prematuritymentioning
confidence: 99%